(3eYQaI GdYed HGdUajMI GdbeQjI hGdMb GdcShajIs - (3Ydj Hf YjSis
(3ChdgG (B:s
(3bGd HYO MeO Gddg hGdKfGA Ydjg CeG eYQaI gPg GdUajMI hGdYed HeG ajgG aEf MLQJgG ebSheI HCQHYI CbSGe s
(3BNQgG (B:s
(3hJMQc gPg GdOGFQI hJfXQ GdCab eG hbY Ydjg ef GdSQhL hGdOQhL agh GdWGdY aGage Pdc hbS Ydjg jMUd dcd GdHjGf Ef TGA Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3fSNI NRGFfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs